Strategic Alliances between Banks and Fintech Companies: Effects on Financial Inclusion in Gorontalo - Suci Belfebriani; Sri Astuti (Generasi Sains Indonesia, 2024)
This study explores the impact of strategic alliances between banks and fintech companies on financial inclusion in Gorontalo. Although financial inclusion is essential for economic growth, many rural communities in Indonesia remain outside formal financial systems. Partnerships between banks and fintech firms offer a potential solution by combining regulatory reliability with technological innovation. Using a mixed-method explanatory sequential design, the study surveyed 200 respondents, including microenterprise owners and households, and conducted interviews with bank managers, fintech executives, and customers. Quantitative data were analyzed using descriptive statistics and multiple regression, while qualitative data provided contextual insights. The study measured the strength of strategic alliances through partnership intensity, service integration, and product innovation, and financial inclusion through access, usage, and quality. Results show that strategic alliances significantly improve financial inclusion, with the strongest effect on access, followed by usage and quality. However, barriers such as low digital literacy, weak infrastructure, and high transaction costs limit the full potential of these collaborations. The findings suggest that improving digital literacy and infrastructure support is crucial for strengthening the positive role of bank–fintech partnerships in promoting inclusive financial growth in Gorontalo.